Book Review: Carbon Colonialism: How Rich Countries Export Climate Breakdown - Sharma, Ankita (Studies of Transition States and Societies, 2023)
Carbon Colonialism: How Rich Countries Export Climate Breakdown by Laurie Parsons, 2023, Manchester University Press.